PENGARUH METODE READING ALOUD TERHADAP KEMAMPUAN MEMBACA DAN MINAT BACA SISWA KELAS III UPTD SDN 1 KEDOKANBUNDER - Tobroni; Piyantina Rukmini; Inayatus Sholihah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by students' low reading ability and interest in Indonesian language learning. The objective was to determine the effect of the read-aloud method on the reading ability and interest of third-grade students at the UPTD SDN 1 Kedokanbunder. This study used an experimental method with a pretest-posttest control group design. The sample was randomly selected: class III A as the experimental class and class III B as the control class, each consisting of 30 students. Data were collected through a reading test and a reading interest questionnaire, then analyzed using an independent sample t-test. The results showed that the read-aloud method significantly improved reading ability (sig. = 0.000 < 0.05), but had little effect on students' reading interest (sig. = 0.934 > 0.05). Thus, the read-aloud method is effective in improving reading ability, but not sufficient to increase students' reading interest.